Assessment of Cluster Front Line Demonstrations on Rapeseed (Brassica campestris L.) in Tirap District of Arunachal Pradesh - Kalita, Simanta Kumar; Chhonkar, D.S.; Kanwat, Manish (Indian Journal of Extension Education, 2019)
Rapeseed (Brassica campestris L.) is one of the important oil seed crop cultivated in Tirap district of Arunachal Pradesh. The production and productivity of rapeseed in the district is low and constant attempts are being made to improve the production and productivity, area increase, adopting high yielding varieties and improved cultivation practices. Krishi Vigyan Kendra, Tirap conducted Cluster Front Line Demonstration (CFLD) at the farmers’ field in 24 villages of the district during 2017-18, 2018-19 and 2019-20. The critical inputs and constraints in existing production technology were identified. Lack of high yielding variety, inadequate input availability, pest and disease incidence and lack of technical knowhow were the predominant identified causes of low productivity of rapeseed in Tirap district. The results of three years demonstrations of variety TS-46 revealed yield increased by 30.97 per cent (2017-18), 28.61 per cent (2018-19) and 26.78 per cent (2019-20) respectively. The additional return in demonstrated plots under TS-46 ranged between Rs. 5732 to Rs. 7285 per hectare during different years. The technology index ranging from 3.6 to 12.9 per cent was found between CFLD demonstration plots and farmers’ practices during the different time line. It can be concluded that rapeseed production can be enhanced by encouraging farmers through adoption of high yielding variety TS-46, improved technologies and ensuring need based inputs in due time.
Keywords: CFLD; Rapeseed; Growth; Yield; Economics; Gap